Modeling time varying risk of natural resource assets: Implications of climate change - Anke D. Leroux; Vance Martin; Kathryn A. St. John (Quantitative Economics, 2022)
A multivariate GARCH model of natural resources is specified to capture the effects of time varying portfolio risk. A special feature of the model is the inclusion of realized volatility for natural resource assets that are available at multiple frequencies as well as being sensitive to sudden changes in climatic conditions. Natural resource portfolios under climate change are simulated from bootstrapping schemes as well as being derived from global climate model projections. Both approaches are applied to a multiasset water portfolio model consisting of reservoir inflows, rainwater harvesting, and desalinated water. The empirical results show that while reservoirs remain the dominant water asset, adaptation to climate change involves increased contributions from rainwater harvesting and more frequent use of desalinated water. It is estimated that climate change increases annual water supply costs by between 7% and 44% over a 20-year forecast horizon.
Keywords: 330; climate change; natural resource portfolio; realized variance; RV-DCC; C32; C53; Q35; Q54